Integration Analysis of Sharia Stock Price Index in Indonesia, Malaysia, China and The United States Islamic Capital Markets - Darmawan, Zulfikri Charis (IAIN Langsa, 2023)
Purpose – This study aims to determine the effect of Dow Jones Islamic Word Malaysia Index (DJMY25D), Dow Jones Islamic Market China (DJICHKU) and Dow Jones Islamic Market Index (DJIMI) on Indonesian Sharia Stock Index (ISSI.JK) for the 2018-2022 period. Design/methodology/approach – The exogenous variables in this study include DJMY25D, DJICHKU and DJIMI. Meanwhile, the endogenous variable is ISSI.JK. In the DJMY25D, DJICHKU, DJIMI and ISSI.JK variables it is calculated by the percentage growth in closing prices at the beginning of the month. The population in this study is the Global Islamic Index which is part of the Dow Jones Global Index which consists of 34 countries using purposive sampling technique. In addition, Ordinary Least Square (OLS) Regression Analysis was used in the data analysis method. Findings – The results of this study indicate that simultaneously DJMY25D, DJICHKU and DJIMI have a significant effect on ISSI.JK. Partially, DJMY25D and DJICHKU have an effect on ISSI.JK but not significantly. while DJIMI has a significant effect on ISSI.JK. Research limitations/implications – his research is limited by the integration of Indonesian Islamic stocks with several Malaysian, Chinese and American Islamic stocks. There are several other countries where the Islamic stock market may be integrated with Indonesian Islamic stocks, but in this study only uses diversification of financing based on contracts and usage due to limited data and research time. Practical implications – The integration of ISSI.JK and DJIMI sharia stocks may be useful for market players and regulators to consider the DJIMI stock market in estimating market price movements and volatility of the Indonesian sharia stock market. Originality/value – This study provides new insights on the integration of Islamic stocks in Malaysia, China, America and Indonesia in 2018-2022.